History of Gestational Diabetes Mellitus in Relation to Cardiovascular Disease and Cardiovascular Risk Factors in US Women - Shostrom, Derrick C. V.; Sun, Yangbo; Oleson, Jacob J.; Snetselaar, Linda G.; Bao, Wei (Frontiers in Endocrinology, 2017)
Background: Findings from previous studies examining the association between gestational diabetes mellitus (GDM) and subsequent risk of cardiovascular disease (CVD) have been inconsistent and inconclusive. We aimed to examine the associations of a previous history of GDM with risk of CVD and status of cardiovascular risk factors in a nationwide population-based study in the United States. Methods: This study included 8,127 parous women aged 20 years and older in the 2007-2014 cycles of the National Health and Nutrition Examination Survey in the United States. The exposure was self-reported diagnostic history of GDM and the outcomes were self-reported diagnostic history of CVD and measurements of CVD risk factors, including blood pressure and blood lipids. Regression models with sample weights were used to examine the associations of GDM with CVD and CVD risk factors. Results: The prevalence of CVD was higher among women with a history of GDM than those without GDM. Among women with a history of both GDM and CVD, CVD was diagnosed on average 22.9 years after the diagnosis of GDM. After adjustment for demographic, socioeconomic, and lifestyle factors, a history of GDM was associated with 63% higher odds of CVD (odds ratio 1.63, 95% confidence interval (CI) 1.02, 2.62, p-value=0.04). Further adjustment for body mass index (BMI) modestly attenuated the association (odds ratio 1.52, 95% CI 0.95, 2.44, p-value=0.08). A history of GDM was significantly associated with lower serum level of HDL-cholesterol (adjusted β-coefficient -3.33, 95% CI -5.17, -1.50, p-value≤0.001), but not associated with total cholesterol, LDL-cholesterol, triglycerides, or systolic or diastolic blood pressure. Similarly, the association between a history of GDM and HDL- cholesterol was attenuated after adjustment for BMI (adjusted β-coefficient -1.68, 95% CI -3.38, 0.03, p-value=0.54). Conclusions: Women with a previous history of GDM have significantly higher risk for developing CVD and lower serum level of HDL-cholesterol, compared to women without a history of GDM. The associations may be explained, at least partly, by BMI.